The growth and physiological responses of tambaqui Colossoma macropomum fed on the high dose of clove oil-supplemented diet - Puteri, Andi Tiara Eka Diana; Jusadi, Dedi; Nuryati, Sri (Indonesian Society of Scientific Aquaculture (ISSA), 2016)
ABSTRACT In this study, tambaqui Colossoma macropomum juvenile were given feed supplemented with clove oil Syzygium aromaticum at a dose of 0 and 100 mg/100 g diet. This study purposed to assessment the effect of clove oil supplementation at high dose (100 mg/100 g diet) on growth performance and health status of freshwater tambaqui. As many as 25 fishes with initial body weight 7.62±0.44 g maintained in 15 aquariums for 45 days. Each treatment consisted of three replications. Data were analyzed by t-test. The results showed that tambaqui growth performance on both treatments were not significantly different. However, supplementation of high doses 100 mg clove oil/100 g diet showed reduce on the blood parameters and declining the abundant of intestinal microflora in tambaqui gut, but the types seen more diverse. The observation of fish liver histology showed that hepatocyte cells in the treatment of 100 mg clove oil become smaller and dense compared with 0 mg clove oil treatment. The use of high doses of clove oil does not interfere with the tambaqui growth performance despite the downturn in the physiological responses were observed. Keywords: clove oil, Syzygium aromaticum, Colossoma macropomum, growth performance ABSTRAK Di dalam penelitian ini, benih ikan bawal tawar Colossoma macropomum dipelihara dengan pemberian pakan yang ditambah minyak cengkeh Syzygium aromaticum pada kadar 0 dan 100 mg/100 g pakan. Tujuannya untuk melihat pengaruh penambahan minyak cengkeh di dalam pakan pada dosis tinggi (100 mg/100 g pakan) terhadap performa pertumbuhan dan respons fisiologis ikan bawal. Sebanyak 25 ekor ikan bawal dengan bobot individu awal 7,62 ± 0,44 g dipelihara pada 15 akuarium selama 45 hari. Data yang diperoleh dianalisis dengan uji komparasi t-test antar dua perlakuan dengan tiga ulangan. Hasil penelitian menunjukkan bahwa tidak ada pengaruh dari kedua perlakuan terhadap parameter pertumbuhan. Namun, pemberian pakan yang mengandung minyak cengkeh dosis tinggi 100 mg/100 g pakan mempengaruhi respons fisiologis berupa rendahnya kisaran nilai gambaran darah serta menurunnya jumlah mikroflora di usus ikan bawal, meski jenisnya lebih beragam. Hasil pengamatan histologi hati ikan pada perlakuan 100 mg minyak cengkeh menunjukkan bahwa sel hepatosit berukuran lebih kecil dan terlihat rapat dibandingkan dengan perlakuan 0 mg minyak cengkeh. Penggunaan minyak cengkeh dosis tinggi tidak menganggu performa pertumbuhan ikan bawal meskipun terjadi penurunan pada respons fisiologis yang diamati. Kata penting: minyak cengkeh, Syzygium aromaticum, Colossoma macropomum, performa pertumbuhan